2021
DOI: 10.1093/plphys/kiab161
|View full text |Cite
|
Sign up to set email alerts
|

TWAS results are complementary to and less affected by linkage disequilibrium than GWAS

Abstract: A genome-wide association study (GWAS) is used to identify genetic markers associated with phenotypic variation. In contrast, a transcriptome-wide association study (TWAS) detects associations between gene expression levels and phenotypic variation. It has previously been shown that in the cross-pollinated species, maize (Zea mays), GWAS and TWAS identify complementary sets of trait-associated genes, many of which exhibit characteristics of true positives. Here, we extend this conclusion to the self-pollinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…For example, Y1 encodes a phytoene synthetase involved in carotenoid biosynthesis 60 (Figure 7a & e). This gene is associated with endosperm color via GWASs (this study) and transcriptome wide association studies (TWAS) 75 and this study (Figure 7a). Temperate maize was specifically selected for the y1 allele, resulting in the greater accumulation of carotenoids in the endosperm compared to that of tropical maize 76 (Figure 7b).…”
Section: Discussionsupporting
confidence: 51%
“…For example, Y1 encodes a phytoene synthetase involved in carotenoid biosynthesis 60 (Figure 7a & e). This gene is associated with endosperm color via GWASs (this study) and transcriptome wide association studies (TWAS) 75 and this study (Figure 7a). Temperate maize was specifically selected for the y1 allele, resulting in the greater accumulation of carotenoids in the endosperm compared to that of tropical maize 76 (Figure 7b).…”
Section: Discussionsupporting
confidence: 51%
“…The use of gene expression data, offering gene-level resolution and insight into regulatory variation, has the potential to help overcome these obstacles. Transcriptome-wide association studies (TWAS), which assess the association between gene expression and terminal phenotypes (Hirsch et al 2014;Lin et al 2017;Pasaniuc and Price 2017;Li et al 2021), have successfully identified associations previously found in GWAS and have highlighted new and promising associations for mature grain carotenoids and tocochromanols (Kremling et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been increasingly realized that variation in transcript abundance provides significant clues regarding genes that underlie whole-organism phenotypic outcomes [ 41 , 42 ]. Accordingly, we created the web tool, T-CLIM, which integrates transcriptome landscapes and environmental clines in Arabidopsis .…”
Section: Resultsmentioning
confidence: 99%
“…This limitation can be partially ameliorated by TWAS analyses, as we have done here (Figs. 1 and 2 ), which are less susceptible to issues of linkage disequilibrium [ 41 , 42 ]. RiboSNitch and GWA analyses in humans are further complicated by heterozygosity; here, Arabidopsis has an advantage as it is naturally inbred, avoiding the need for disambiguation of alleles within an accession.…”
Section: Discussionmentioning
confidence: 99%